2012
DOI: 10.1111/j.1755-3768.2012.02437.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus on corneal biomechanics and measurement of intraocular pressure

Abstract: ABSTRACT.Purpose: To determine whether corneal hysteresis (CH) and corneal resistance factor (CRF) are altered in diabetes and whether these parameters are related to HbA1c. Methods: One randomly chosen eye of 35 healthy subjects and 31 patients with diabetes was examined. Patients with diabetes were divided into group 1 with HbA1c <7% (n = 14) and group 2 with HbA1c ‡7% (n = 17). CH and CRF were measured using ocular response analyzer (ORA); central corneal thickness (CCT) using ultrasound pachymetry; increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 38 publications
7
70
1
2
Order By: Relevance
“…The CH is believed to reflect the damping properties of the cornea compatible with a shock absorber, which is influenced by the viscosity of the ground substance (reflecting the glycosylation of proteoglycans and glycosaminoglycans), and the CRF is believed to indicate the total resistance of the cornea to deformation. 25 The facts that the CH and the CRF were decreased significantly with age 26 were compatible with our results showing that aging decreased the viscosity of the eyeball and the resistance to outer pressure, which caused a larger corneal displacement in older subjects at the 30.0 ms time point. Furthermore, the fact that the thicker CCT causes higher CH and CRF values, while the axial length and sex have no significant effects on the CH and CRF, also supports our results.…”
Section: Discussionsupporting
confidence: 93%
“…The CH is believed to reflect the damping properties of the cornea compatible with a shock absorber, which is influenced by the viscosity of the ground substance (reflecting the glycosylation of proteoglycans and glycosaminoglycans), and the CRF is believed to indicate the total resistance of the cornea to deformation. 25 The facts that the CH and the CRF were decreased significantly with age 26 were compatible with our results showing that aging decreased the viscosity of the eyeball and the resistance to outer pressure, which caused a larger corneal displacement in older subjects at the 30.0 ms time point. Furthermore, the fact that the thicker CCT causes higher CH and CRF values, while the axial length and sex have no significant effects on the CH and CRF, also supports our results.…”
Section: Discussionsupporting
confidence: 93%
“…As the amount of the AGE formation is not known, these inconsistent results of the biomechanical properties of the cornea seem not to be surprising in a group of different patients with diabetes. In a previous study CH was higher, and the CRF was significantly higher in diabetics when compared with the control group [23]. In contrast, another earlier study reported significantly lower CH values in diabetics [22].…”
Section: Discussionmentioning
confidence: 88%
“…Diabetic patients were reported to exhibit an increase in CH, indicating an increase in the viscosity of the ground substance. Increased viscosity is associated with higher corneal shearing strength and increased dampening [23]. This increased dampening effect, which is indicated by a high CH, is most likely due to glycosylation of proteoglycans and glycosaminoglycans (GAGs).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observed similar trends with statistical significance and suggested an increased dampening effect and increased viscoelasticity of such corneas. 27,47,48 Scheler et al 48 stated that the increased dampening effect was most likely due to the glycosylation of proteoglycans and glycosaminoglycans of the corneal extracellular matrix. Additionally, corneal collagen is modified in diabetic patients, and the accumulation of advanced glycation end products on basement membrane, especially laminin, can play a role in the corneal biomechanic modification of diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%